Compulsory Medical Malpractice Civil Liability Insurance - Nasser Abdullah Ayed Al-Qahtani (International Journal of Law Research and Studies, 2025)
Compulsory civil liability insurance in the field of medical errors is considered a fundamental pillar of the modern health care system, as it aims to protect the rights of patients and compensate them in the event of damages resulting from medical errors. This research studied the compulsory insurance contract against civil liability for medical errors in the Kingdom of Saudi Arabia, through the analytical approach to the relevant Saudi regulations and decisions. This research was divided into an introductory section and two main sections. In the introductory section, I dealt with the nature of medical work. In the first section, I dealt with compulsory insurance against civil liability for medical errors, and in the second section, some judicial precedents related to the insurance policy for the risks of practicing medical professions. The study came out with many results, the most important of which is that for medical civil liability to exist, there must be elements, namely the error attributed to the health practitioner, the harm he caused to the patient, and the causal relationship between them. It also reached a number of recommendations, the most important of which is considering establishing a special and strict penalty in the event of Failure of health practitioners to conclude an insurance contract against medical malpractice.
Keywords: Compulsory Insurance; Civil Liability; Medical Errors